The efficacy of colchicine and dapsone combination therapy in relapsed immune thrombocytopenia - Thanawat Rattanathammethee (2018)
© T. Rattanathammethee et al., 2017. The aim of the present paper is to evaluate the efficacy and safety of colchicine and dapsone combination therapy in cases of steroid-dependent, relapsed and refractory immune thrombocytopenia (ITP). This is a retrospective study of ITP patients who attended the Hematology Clinic at Chiang Mai University Hospital (Thailand) from 1 January 2008 to 30 September 2014. Medical records and clinical data were reviewed for efficacy and adverse effects. Sixty-four ITP patients received the combination therapy. The median age was 46 years and 70.3% were female. The majority (65.6%) were relapsed ITP patients. Median platelet count before starting treatment was 22.6×10 9 /L. The response rate was 82.8%, with 75.0% of patients having a complete response. Median time to response was 8 weeks. The response rate was higher in relapsed patients (90.4%) compared to refractory (61.5%) and steroid-dependent patients (77.8%). Steroid treatment was discontinued in 30 patients (50%) following combination therapy. The most common side effect was hemolysis due to dapsone which was found in eight patients (12.5%). We can therefore conclude that combination therapy with colchicine and dapsone is an alternative second-line therapy option in relapsed ITP cases with acceptable side effects.